Lived Experiences and Philosophies: Basis for Life Skills Guide for Beginning Teachers - Roldan C Cabiles (Universitas PGRI Semarang, 2022)
This phenomenological research produced a Life Skills Guide for Beginning Teachers to orient them to local realities in rural, coastal, and urban schools. Based on the analysis, the life history of teachers reflects grit and resilience along with their external and internal motivations in their choices, particularly in their professional development. Family for them is a significant source of motivation to overcome the challenges and concerns in the educational landscape. The key informants in the three (3) geographical locations demonstrated adaptability or flexibility, good communication, interpersonal or social skills, pedagogical skill, and practicality. Teacher-participants in the rural and urban areas are digitally literate and competitiveness was mainly reflected in the urban areas. Moreover, financial literacy is strongly reflected among the teacher-participants from the rural and coastal areas probably because there are few to none distractions which may tempt them to spend. Among urban teachers, it was noted that they are susceptible to spending their money because they are surrounded with commercial establishments and entertainment centers. Based on the life history and demonstrated life skills, teachers in the rural, urban and coastal areas reflect essentialist, humanistic/existentialist, pragmatist/progressivist, reconstructionist, constructivist, idealist, behaviorist, and perennial philosophies. It was significantly observed that selected teacher-participants in the rural and coastal areas also exhibit positivism that is influenced by their field of expertise which is mathematics and science. Given these findings, the life skills guide for beginning teachers is proposed to help the beginning teachers cope with the actual realities of their teaching assignments.